Blade of Grass as an Unusual Cause of Recurrent Facial Cutaneous Sinus Tract: A Clinical Case - Resmije Ademi-Abdyli; Feriall Perjuci; Teuta Bicaj; Yll Abdyli (Hindawi Limited, 2016)
The presence of an embedded foreign body in the oral and maxillofacial region is not unusual, but the impaction of a foreign body with vegetative nature is rare. Prompt diagnosis and surgical removal of these foreign bodies will minimize their associated complications. This case report presents a patient with recurrent submandibular abscess and persistent facial cutaneous sinus tract caused by a retained blade of grass inside the facial soft tissue. The fact that the plain radiograph misdiagnosed the presence of a foreign body meant that the pathology persisted for about three months, and the patient underwent hospitalization, surgical procedures, and antibiotic regimens; however all of these failed until the foreign body was detected and removed. Conclusion. To avoid misdiagnosis of foreign body presence in the orofacial region, notably suspected foreign bodies with low radiopacity, the clinician must perform careful clinical examination and use the ultrasonography. Also, in the uncertain cases where the pathology persists, despite having undertaken surgical procedures and antibiotic regimens, the clinician should pay more attention to the patient's history which may suggest the presence of the foreign body.